Understanding Self-Rated Health and Unconventional Oil and Gas Development in Three Colorado Communities. Issue 1 (2nd January 2021) - Mayer, Adam; Malin, Stephanie; McKenzie, Lisa; Peel, Jennifer; Adgate, John
Abstract: Domestic, onshore oil and gas production has increased substantially in the United States in the last ∼20 years, creating a range of positive and negative impacts on communities. In this paper, we add to the growing literature on unconventional oil and gas production (a.k.a., "fracking") and well-being by evaluating the association between self-reported stress induced by local oil and gas development and subjective well-being in the form of self-rated health. We also ask how the intensity of local drilling and trust in regulators influences self-rated health. Using novel survey data, we compare three Colorado communities with differential amounts of oil and gas development. Results from ordinal logistic regression models suggest that living in a community that hosts extraction is associated with lower self-rated health and that stress from local oil and gas operations is associated with lower self-rated health. To some degree, trust in regulators seems to improve self-rated health. We discuss implications for research and policy.